Pengaruh Publik Figur, Citra Merek Dan Ekuitas Merek Terhadap Keputusan Pembelian Sepeda Motor Yamaha Di Kota Medan - Muhammad Arif; Willy Yusnandar; Ayu Waningsih Sirait (-, 2020)
This study aims to examine the relationship between work environment, work discipline and the purpose of this study is to find out and analyze the influence of public figures on purchasing decisions, to find out and analyze brand image on purchasing decisions, to find out and analyze brand equity on purchasing decisions and to find out public figure, brand image and brand equity towards jointly against the decision to purchase Yamaha motorbikes in Medan. The approach used in this research is an associative approach. The population in this study were all consumers who used Yamaha NMAX motorbikes in West Medan District, while the sample was determined by nonprobability sampling so that the number of respondents was 80 people using incidental sampling. Data collection techniques in this study used interviews, documentation and questionnaires. Data analysis techniques in this study used the Classic Assumption Test, Multiple Linear Regression, t Test and F Test, and Determination Coefficient. Data processing in this study uses SPSS 21 software program. The results of this study indicate that Public Figur has a positive and significant influence on purchasing decisions for Yamaha NMAX Motorcycles Brand Image has a positive and significant influence on purchasing decisions for Yamaha NMAX Motorcycles. Brand Equity has a positive and significant influence on purchasing decisions for Yamaha NMAX Motorcycles